Human Neutrophil Antigen Genotype and Allele Frequencies in Iranian Blood Donors - Behnaz Esmaeili; Behnaz Bayat; Atefe Alirezaee; Mona Delkhah; Mohammad Reza Mehdizadeh; Zahra Pourpak (Journal of Immunology Research)
Objective. Human neutrophil antigens (HNAs) can be targeted by HNA-allo antibodies and cause a variety of clinical conditions such as transfusion-related acute lung injury (TRALI) and neonatal alloimmune neutropenia (NAIN). The current study is aimed at identifying the genotype and allele frequencies of HNAs in Iranian blood donors. Methods. A total of 150 blood samples were obtained from healthy blood donors. HNA-1, HNA-3, HNA-4, and HNA-5 were genotyped, using the polymerase chain reaction sequence-specific primer (PCR-SSP) technique. The expression of the HNA-2 antigen on the neutrophil surface was evaluated by flow cytometry. Results. The allele frequencies of FCGR3B∗1 (encoding HNA-1a), FCGR3B∗2 (encoding HNA-1b), and FCGR3B∗3 (encoding HNA-1c) were 0.34, 0.63, and 0.03, respectively. For HNA-3, the allele frequencies for SLC44A2∗1 (encoding HNA-3a) and SLC44A2∗2 (encoding HNA-3b) were 0.63 and 0.37, respectively. The frequencies of ITGAM∗1 (encoding HNA-4a) and ITGAM∗2 (encoding HNA-4b) alleles were 0.85 and 0.15, respectively. Furthermore, the frequencies of ITGAL∗1 (encoding HNA-5a) and ITGAL∗2 (encoding HNA-5b) alleles were 0.72 and 0.28, respectively. In the studied population, HNA-2 antigen was present on the neutrophil surface in 97.3% of the individuals, while no detectable HNA-2 expression was observed in 2.7% of the individuals. However, no significant difference in HNA-2 expression between different age groups was found. Conclusion. The present study provides the first report of the HNA allele and genotype frequencies among the Iranian population. All HNAs (HNA-1 to HNA-5) were typed using the PCR-SSP and flow cytometer. In the current cohort study, the determined HNA allele frequencies were similar to the previous reports from British, German, and Danish populations. Considering the presence of different Iranian ethnic groups, further studies with a larger sample size are needed to draw a total picture for HNA allele frequencies.